Factors Affecting Readiness of Teachers in Distance Education and its Effect on the Learner's Performance - Escobido, M (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
The main thrust of this study was to determine factors affecting teachers' readiness in distance education and its effect on the learners’ learning performance. This study utilized a descriptive-correlational approach in determining perceptions of the factors affecting teachers’ readiness for distance education. Moreover, the instrument utilized to gather data was a modified survey questionnaire. It was found that there is a significant relationship between learners’ learning performance and the perceived factors affecting teachers’ readiness for distance learning. Among the factors affecting teachers' readiness for distance learning, only the management of learning greatly influences learners’ learning performance. The researcher recommended that DepEd should boost the teachers’ attitude towards modular distance learning delivery modality by providing the needs of the teachers; school administrators should come- up with adequate training courses, webinars, seminars, and/or workshops should be provided to the teachers considering their teaching-learning needs in the new normal; teachers must be supported and guided to boost their varied teaching styles and weaknesses as they adjust into the new normal and should uplift their attitude more towards distance learning modality since they play a more significant part in its success and parents should also have to take part during this time of crisis, they should provide assistance and support to their child as they have this significant role to fill in as replacements to their teachers.